The Awareness and Attitude of, Midwives Working in Private Offices in Tehran Province, Iran Toward Abortion Laws and Related Factors - Name, Masoumeh; Ahmadi Doulabi, Mahbobeh; Jafari, Asiye; Salmani, Fatemeh (Advances in Nursing & Midwifery, 2020)
Abstract Introduction: Legal abortion is performed to prevent maternal and fetal disorders. Midwives’ awareness and attitude toward abortion laws have undeniable effects on the decisions made by women with high-risk pregnancies. By recent study, The present study evaluated the awareness and attitudes of midwives working in private offices in Tehran Province, Iran, toward abortion laws and related factors. Methods: This descriptive-analytical study was done in 2016. A total of 236 midwives were selected from Tehran Province took simple random sampling. The data were collected took using a valid and reliable researcher-made questionnaire by items related to demographic characteristics, awareness, and attitude. The collected data were analyzed by descriptive tests (mean, standard deviation, confidence interval, frequency, and relative frequency) and linear regression analysis. Results: The midwives’ mean scores of awareness and attitude were 57.7 ± 7.44 (95% CI: 56.61-58.54) and 99.08 ± 10.09 (95% CI: 97.83-100.38), respectively. Midwives’ age (B = 0.21), work shifts in the midwifery office (B = 1.29), being a member of the Midwifery Learner Society (B = 3.05), and cooperating with local legal medicine centers (B = 3.63) were found to be the predictors of awareness scores. Gain experience in the midwifery office was the only predictor of midwives’ attitude, i.e., every one-year increase in work experience decreased the scores of attitude by 1.61 points. Conclusions: The participating midwives had a moderate level of awareness, which was affected by different variables. Cooperating with local legal medicine centers had the most significant effect on improving midwives’ awareness. Moreover, the midwives had low scores of attitude, and a few variables predicted their attitude.